New species and additional evidence of aphid parasitoids (Hymenoptera: Braconidae: Aphidiinae) from India - Rakhshani, Ehsan; Barahoei, Hossein; Ahmed, Zubair; Tomanović, Željko; Janković, Marina; Petrović, Andjeljko; Bodlah, Imran; Starý, Petr (Zootaxa, 2012)
A survey was carried out on Aphidiinae of India. Fifteen species belonging to nine genera were identified, of which Aphid-ius bifurcatus Rakhshani & Tomanović and Ephedrus longiarticulatus Rakhshani & Tomanović are newly described andillustrated. Aphidius funebris Mackauer was recorded for the first time from India. A brief taxonomic note with regard to the morphological variability of diagnostic characters as well as comments on geographical distribution are presented.